Methodology for assessing the potential of innovative development of a small enterprise - O. A. Dubova (Путеводитель предпринимателя)
Today many enterprises face a number of issues in the process of their management. This is provoked by the fact that many enterprises need for their development any new implementation. These innovations can be implemented both in the production process and in the management process, and for the enterprise, this will be its innovation sphere. The development of the innovation sphere will allow to return the advanced capital more quickly and send it again to expand or improve the activity. Management in the innovation sphere is directed and evaluated according to the criteria of economic efficiency, therefore, it is important to give appropriate consideration to management decisions. This can not be done without a preliminary assessment of the innovative potential of the enterprise.